Samisk påvirkning på skandinavisk grammatikk? - Enger, Hans-Olav (Folkmålsstudier, 2023)
Saami influence on Scandinavian grammar? Older histories of the Scandinavian languages (Danish, Swedish and Norwegian) commonly assume that German has influenced the Scandinavian languages heavily. By contrast, they do not assume any significant influence from the Saami languages. This traditional view has, however, been challenged in an interesting monograph by Kusmenko (2008). While Kusmenko’s hypotheses have been met with scepticism by some specialists of Scandinavian, they have also been received favourably by some, notably Bull (for example in this journal, 2017). Yet Bull also points to an important weakness in Kusmenko’s argument – the near-absence of lexical influence despite the supposedly heavy grammatical influence. However, Bull argues that this absence is apparent rather than real; in Norwegian dialects in the very North, Saami loan-words are more numerous. In this paper, I argue that evidence from these dialects is not necessarily very relevant, since Kusmenko’s hypotheses primarily concern dialects further south. While Kusmenko and Bull are justified in criticising the ideological bias in much language historiography in Norway, and while it now seems clear that prestige relations between speakers of Saami and Scandinavian need not have been the same a millennium ago as they were a century ago, the more strictly linguistic evidence adduced by Kusmenko is still not convincing. The absence of good parallels make his scenario look less plausible.